National Identity Crisis of Indonesian Education in the Global Era - Jumari, Jumari; Juliangkary, Eliska; Pujilestari, Pujilestari; Sriartha, I Putu (LETIGES, 2024)
This study examines the national identity crisis in Indonesian education globally. This type of research is literature with a qualitative approach. Data collection by reconstructing data from books, archives, magazines, documents, journals, documentation, newspapers, etc. Using the philosophical hermeneutic analysis approach of Hans-Georg Gadamer through the stages of interpretation, holistic, and heuristic. This study shows that education is needed to strengthen national identity in the vortex of social change. Globalization is like a